2002
DOI: 10.2113/gscanmin.40.4.1091
|View full text |Cite
|
Sign up to set email alerts
|

ORIGIN OF SEPIOLITE AND LOUGHLINITE IN A NEOGENE VOLCANO-SEDIMENTARY LACUSTRINE ENVIRONMENT, MIHALlCClK ESKISEHIR, TURKEY

Abstract: The Middle to Upper Miocene volcano-sedimentary units in the Mihalıççık-Eskişehir area of Turkey consist mainly of altered tuff and claystone, with thin layers of dolomite and silica nodules and horizons. Ripple marks and desiccation cracks are common in the siliceous tuff and dolomite units. Green to yellowish green claystone exhibits either hard layered or friable features. Sepiolite and loughlinite are dominant in the claystone of the study area. These minerals are generally associated with opal-CT, analcim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 21 publications
(14 reference statements)
3
14
0
Order By: Relevance
“…As mentioned earlier, loughlinite has only been described from three localities world-wide, all of which are playa-lake settings (Eugster and Hardie, 1975;Kadir et al, 2002;Buch and Rose, 1995) similar to that described here. Interestingly, the mineral analcime has been described from all of these localities as well (Echle, 1967;Buch and Rose, 1995;Iijima and Hay, 1968), which would suggest similar physico-chemical requirements for the formation of both loughlinite and analcime.…”
Section: Sepiolite and Loughlinite Occurrences And Associationssupporting
confidence: 70%
See 3 more Smart Citations
“…As mentioned earlier, loughlinite has only been described from three localities world-wide, all of which are playa-lake settings (Eugster and Hardie, 1975;Kadir et al, 2002;Buch and Rose, 1995) similar to that described here. Interestingly, the mineral analcime has been described from all of these localities as well (Echle, 1967;Buch and Rose, 1995;Iijima and Hay, 1968), which would suggest similar physico-chemical requirements for the formation of both loughlinite and analcime.…”
Section: Sepiolite and Loughlinite Occurrences And Associationssupporting
confidence: 70%
“…The mineral has subsequently only been described from two additional localities, viz. i) Killik (Turkey), where it occurs within a Middle to Upper Miocene volcanosedimentary lacustrine basin (Echle, 1967;Kadir et al, 2002), and ii) from the Etosha Pan region in Northern Namibia (Buch and Rose, 1996). The limited distribution of the mineral is confirmed by Anthony et al (1995), who make mention of only the occurrences in Wyoming and Turkey.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Loughlinite is the Na-sepiolite, in which Mg is partially replaced by Na and also contains Na in the channels (Fahey and Axerod, 1948). Kadir et al (2002) Suarez and GarciaRomero (2006) reported that isomorphic substitutions in octahedral palygorskite sheets occur only in M2 posi tions. Fe may occupy M2 positions whereas Mg can occupy all possible sites: M1, M2, and M3.…”
Section: Introductionmentioning
confidence: 99%